Estrategias de afrontamiento al estrés en enfermeras del área de urgencias de la Clínica Santa Sofia del Pacifico de la Ciudad de Buenaventura (2021)
Nursing personnel al the national level play a vital role in caring for people who are in a delicate state of health and are admitted to medical centers, bearing on their shoulders a large part of the responsibility for caring for these people. This is why they are exposed to high levels of work stress, which can generate negative consequences for them, both physically and emotionally, constituting a risky situation for workers in this health area. The present study had the general objective of describing the stress-coping strategies of emergency room nurses at the Santa Sofia del Pacifico Clinic. This was carried out with the quantitative method, the type of study used was descriptive-exploratory, the sample was comprised of 40 nurses from the emergency department.